Osteochondritis Dissecans of the Talus: A New Transmalleolar Fixation Technique - Philippe Moisan MD; Stéphanie Lamer MD; Orville Li; Guy Grimard MD; Marie-Lyne Nault MD, PhD (SAGE Publishing, 2022)
Background: Conservative management is the first line of treatment in most osteochondritis dissecans (OCD) cases and can be sufficient for small and stable lesions in skeletally immature patients. Unstable lesions commonly require surgical interventions and may need fixation. The standard surgical approach to fix posteromedial lesions of the talus involves an osteotomy of the medial malleolus. This technique is invasive and requires multiple weeks of immobilization after the surgery. In this video, we present a minimally invasive transmalleolar approach used for the fixation of an OCD lesion of the talus. Indications: The main indication for this procedure is the failure of conservative management with persistent ankle pain and functional impairment of an unstable osteochondral lesion with poor potential for revascularization. Technique Description: There are 3 key steps to this surgery: ankle arthroscopy, retroarticular drilling, and transmalleolar fixation. The transmalleolar approach is achieved by creating a tunnel through the medial malleoli oriented toward the lesion. To do so, the surgeon combines fluoroscopy and ankle arthroscopy to first insert a Kirschner wire (K-wire) through the medial malleoli. Once the correct orientation is confirmed, a 4.5-mm cannulated drill bit is used to create the tunnel. Arthroscopic visualization is used to avoid iatrogenic cartilage damage during drilling. Once the tunnel is created, ankle dorsiflexion and plantar flexion are used to access the entire lesion and insert screws. The malleolar tunnel is then filled with a bone graft and the wound closed. The patient is immobilized for 2 weeks after which gentle range of motion is initiated. The patient remains non-weight-bearing for 2 months and is then allowed to bear weight using a boot. Results: Transmalleolar fixation for osteochondritis dissecans of the talus is a minimally invasive procedure that does not require an osteotomy of the medial talus. This approach permits early postoperative range of motion and decreases postoperative pain and edema, but the adequate positioning of the tunnel can prove challenging. Conclusion: Transmalleolar approach to the talus is minimally invasive and allows adequate fixation of certain osteochondral lesions. Studies comparing the reoperation and complication rate with the standard malleolar osteotomy are lacking and need to be performed. The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.